Optimization of Monascus purpureus for Natural Food Pigments Production on Potato Wastes and Their Application in Ice Lolly - Abdel-Raheam, Hossam E. F.; Alrumman, Sulaiman A.; Gadow, Samir I.; El-Sayed, Mohamed H.; Hikal, Dalia M.; Hesham, Abd El-Latif; Ali, Maysa M. A. (Frontiers in Microbiology, 2022)
During potato chips manufacturing, large amounts of wastewater and potato powder wastes are produced. The wastewater obtained at washing after cutting the peeled potatoes into slices was analyzed, and a large quantity of organic compounds and minerals such as starch (1.69%), protein (1.5%), total carbohydrate (4.94%), reducing sugar (0.01%), ash (0.14%), crude fat (0.11%), Ca (28 mg/L), Mg (245 mg/L), Fe (45.5 mg/L), and Zn (6.5 mg/L) were recorded; these wastes could be considered as valuable by-products if used as a fermentation medium to increase the value of the subsequent products and to exceed the cost of reprocessing. In this study, we used wastewater and potato powder wastes as a growth medium for pigment and biomass production by Monascus purpureus (Went NRRL 1992). The response surface methodology was used to optimize total pigment and fungal biomass production. The influence of potato powder waste concentration, fermentation period, and peptone concentration on total pigment and biomass production was investigated using the Box-Behnken design method with 3-factors and 3-levels. The optimal production parameters were potato powder waste concentration of 7.81%, fermentation period of 12.82 days, and peptone concentration of 2.87%, which produced a maximum total pigment of 29.86 AU/ml that include, respectively, a maximum biomass weight of 0.126 g/ml and the yield of pigment of 236.98 AU/g biomass. The pigments produced were used as coloring agents for ice lolly. This study has revealed that the ice lolly preparations supplemented with these pigments received high acceptability. Finally, we recommend using wastewater and potato powder wastes for pigment and biomass production, which could reduce the cost of the pigment production process on an industrial scale in the future.